Helicobacter pylori, transmission routes and recurrence of infection: state of the art - Kayali, Stefano; Manfredi, Marco; Gaiani, Federica; Bianchi, Laura; Bizzarri, Barbara; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Helicobacter pylori (H. pylori) infection is one of the most common infection in humans, affecting more than half of the population. The prevalence of the infection varies widely in rural developing areas (more than 80%) compared to urban developed ones (less than 40%), as a consequence of different socioeconomic and hygienic conditions. H. pylori infection is usually acquired during childhood; infected people usually remain asymptomatic, but about 30% of individuals may develop mild to severe upper gastrointestinal diseases such as gastritis, peptic ulcer, gastric cancer or MALT lymphoma. The transmission route is not clear yet; the person-to-person transmission, especially within the same family appears to be prevalent, but also environmental contamination is possible. The eradication without a specific therapeutic regimen is very unlikely and the reinfection rate after an effective eradication therapy is quite rare. The reinfection rate will increase if there are family members affected.